Development of mouse model for oral allergy syndrome to identify IgE cross-reactive pollen and food allergens: ragweed pollen cross-reacts with fennel and black pepper - Kamei, Anna; Izawa, Kumi; Ando, Tomoaki; Kaitani, Ayako; Yamamoto, Risa; Maehara, Akie; Ide, Takuma; Yamada, Hiromichi; Kojima, Mayuki; Wang, Hexing; Tokushige, Koji; Nakano, Nobuhiro; et al. (Frontiers in Immunology, 2022)
Oral allergy syndrome (OAS) is an IgE-mediated immediate food allergy that is localized to the oral mucosa. Pollen food allergy syndrome (PFAS), a pollinosis-associated OAS, is caused by cross-reactivity between food and pollen allergens. However, the underlying pathogenesis of OAS/PFAS remains unclear. In the present study, we developed a method to comprehensively identify cross-reactive allergens by using murine models of OAS and protein microarray technology. We focused on lip angioedema, which is one of the most common symptoms of OAS, and confirmed that mast cells reside in the tissues inside the lower lip of the mice. Interestingly, when the food allergen ovalbumin (OVA) was injected inside the lower lip of mice with high levels of OVA-specific IgE followed by an intravenous injection of the Evans blue dye, we found immediate dye extravasation in the skin of the neck in a mast cell-dependent manner. In addition, the degree of mast cell degranulation in the oral cavity, reflecting the severity of oral allergic responses, can be estimated by measuring the amount of extravasated dye in the skin. Therefore, we developed murine models of OAS to examine IgE cross-reactive allergens in vivo. Protein microarray analysis showed that serum IgE from mice intraperitoneally sensitized with ragweed pollen, one of the major pollens causing pollinosis, bound highly to protein extracts from several edible plants including black peppercorn and fennel. We confirmed that the levels of black pepper-specific IgE and fennel-specific IgE were significantly higher in the serum from ragweed pollen-sensitized mice than in the serum from non-sensitized control mice. Importantly, analysis of murine models of OAS showed that the injection of black pepper or fennel extract induced apparent oral allergic responses in ragweed pollen-sensitized mice. These results indicate IgE cross-reactivity of ragweed pollen with black pepper and fennel. In conclusion, we developed mouse models of OAS to identify IgE cross-reactive pollen and food allergens, which will help understand the pathogenesis of OAS/PFAS.